Climate change, rice crops, and violence: Evidence from Indonesia. (January 2016) - Caruso, Raul; Petrarca, Ilaria; Ricciuti, Roberto
This article contributes to the literature on the nexus between climate change and violence by focusing on Indonesia over the period 1993–2003. Rice is the staple food in Indonesia and we investigate whether its scarcity can be blamed for fueling violence. Following insights from the natural science literature, which claims that increases in minimum temperature reduce rice yields, we maintain that increases in minimum temperature reduce food availability in many provinces, which in turn raises the emergence of actual violence. We adopt an instrumental variable approach and select the instruments taking into account the rice growing calendar. Results show that an increase of the minimum temperature during the core month of the rice growing season, that is, December, determines an increase in violence stimulated by the reduction in future rice production per capita. Results are robust across a number of different functional specifications and estimation methods. From a methodological point of view, we claim that the inconclusive results obtained in this literature may be caused by an overlook of the correct bundle crop/temperature. Studies concentrating on several countries with different crops and using variations of average temperature as a measure of climate change missed the biological mechanism behind the relationship between climate change and violence.